Development of a Chemical Literacy Assessment on Colloid (CLAC) Instrument to Measure Chemical Literacy - Isna Rezkia Lukman; Mellyzar Mellyzar; Sirry Alvina; Nailis Saa’dah (LPPM Universitas Malikussaleh, 2022)
The 21st century requires four specific skills namely literacy, inventive thinking, effective communication, and high productivity. Literacy includes basic literacy, scientific literacy, economic literacy, technological literacy, visual literacy, information literacy, and multicultural literacy. The purpose of this research is to produce a chemical literacy assessment instrument on colloidal system material that is suitable for use as a chemistry measurement tool for high school students who meet the requirements of feasibility validity, reliability, and level of difficulty. This research is a form of development research or R&D (Research and Development). The development model used in this research is the Oriondo and Dallo Antonio instrument development model, which has five stages: 1) planning the test, 2) trying out the test, 3) establishing empirical validity (establishing test validity), 4) determining reliability (establishing test reliability), 5) interpretation of scores (interpreting the test scores). The data collection instruments used in this study were questionnaire validation sheets, question validation sheets, and development results questions. The reliability value of the person from the score obtained in the trial was 0.55 indicating that the reliability of the person or students was in the medium category. Reliability value item was 0.48 in the medium category. Overall, the average reliability value or Cronbach Alpha is 0.69 in the sufficient category. So it can be concluded that the score obtained from the assessment instrument is reliable because it has fulfilled a minimum coefficient value of 0.60.